# (x-2)(x+5)=(x-3)(x+4)+x2

## Simple and best practice solution for (x-2)(x+5)=(x-3)(x+4)+x2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for (x-2)(x+5)=(x-3)(x+4)+x2 equation:

(x-2)(x+5)=(x-3)(x+4)+x2
We move all terms to the left:
(x-2)(x+5)-((x-3)(x+4)+x2)=0
We multiply parentheses ..
(+x^2+5x-2x-10)-((x-3)(x+4)+x2)=0

We calculate terms in parentheses: -((x-3)(x+4)+x2), so:
(x-3)(x+4)+x2
We add all the numbers together, and all the variables
x^2+(x-3)(x+4)
We multiply parentheses ..
x^2+(+x^2+4x-3x-12)
We get rid of parentheses
x^2+x^2+4x-3x-12
We add all the numbers together, and all the variables
2x^2+x-12
Back to the equation:
-(2x^2+x-12)

We get rid of parentheses
x^2-2x^2+5x-2x-x-10+12=0
We add all the numbers together, and all the variables
-1x^2+2x+2=0
a = -1; b = 2; c = +2;Δ = b2-4acΔ = 22-4·(-1)·2Δ = 12The delta value is higher than zero, so the equation has two solutionsWe use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$The end solution:
$\sqrt{\Delta}=\sqrt{12}=\sqrt{4*3}=\sqrt{4}*\sqrt{3}=2\sqrt{3}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(2)-2\sqrt{3}}{2*-1}=\frac{-2-2\sqrt{3}}{-2}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(2)+2\sqrt{3}}{2*-1}=\frac{-2+2\sqrt{3}}{-2}$

`